2004
DOI: 10.1002/macp.200400178
|View full text |Cite
|
Sign up to set email alerts
|

Graft Polymerization of Methacrylamide onto Poly(ethylene terephthalate) Fibers with Benzoyl Peroxide as Initiator and their Characterization

Abstract: Summary: The effects of polymerization temperature and time, initiator and monomer concentrations, ratio of water and solvent employed on the grafting of methacrylamide onto poly(ethylene terephthalate) fibers by the use of benzoyl peroxide initiator were studied. The graft yield was observed to increase with temperature and monomer concentration. The highest graft yield was obtained with an initiator concentration of 1 × 10−2 mol/L. The rate of grafting was proportional to the power 0.48 and 1.6 of the methac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
(26 reference statements)
1
11
0
Order By: Relevance
“…25 PET fibers prepared as bundles (0.3 6 0.001 g) were washed with distilled water and Soxhlet-extracted for 6 h with acetone and dried at ambient conditions before graft copolymerization. The fibers were transferred into the reaction chamber containing various amount of MAAm monomer.…”
Section: Preparation Of Methacrylamide Grafted Pet Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…25 PET fibers prepared as bundles (0.3 6 0.001 g) were washed with distilled water and Soxhlet-extracted for 6 h with acetone and dried at ambient conditions before graft copolymerization. The fibers were transferred into the reaction chamber containing various amount of MAAm monomer.…”
Section: Preparation Of Methacrylamide Grafted Pet Fibersmentioning
confidence: 99%
“…In this study, metharylamide was grafted on the PET fibers, and a dye‐ligand was covalently immobilized on the amide groups of the grafted metharylamide brushes. The effects of reaction conditions on the graft polymerization, such as the initiator concentration, ratio of MAA to PET, temperature, and polymerization time were investigated and optimized in the previous study 25. Metharylamide grafted fibers were characterized by FTIR spectroscopy, scanning electron microscopy, and thermogravimetric analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies about chemical grafting,22–24 this type of change trend was also reported. Based on their work, the results of our experiments could be explained by the following reasons: (1) the excessive BPO may act as a terminator of free radicals and decreases the rate of reaction; (2) during the course of crosslinking the flexibility of phosphazene chains decreased, which lowered the diffusion coefficient of BPO, especially for high concentration of BPO 11…”
Section: Resultsmentioning
confidence: 74%
“…[17,18] Therefore, Bz 2 O 2 dissolved in different organic solvents was added to the polymerization tube containing acidic water and monomer to start the polymerization, where the organic solvent=water mixture ratio was kept at a value of 20=80 (v=v). The data for the yield and conductivity of POT given in Table I were obtained.…”
Section: Solvent Type and Dmf/water Volume Ratiomentioning
confidence: 99%